The projects of law on simplified corporation in Brazil and the comparative law:: Will there be access to the capital markets? - Monteiro Martins, José Alberto (Revista de Direito Internacional e Globalização Econômica, 2022)
The focus of this study is to analyze Projects of Law No. 4,303/2012 and No. 348/2012, which content is to institute the Special Regime for the Simplified Corporation, which brings to the discussion the possibility of rethinking the limited liability company for medium and small enterprises. The analysis will consist of investigating, also in the light of comparative law, whether the new corporate model will resolve the issue of difficult access to the capital market. The methodology used in this research is qualitative, exploratory, developed through bibliographic and documentary analysis. The bibliographic and documentary sources used consist of researching books, scientific journals, periodicals and articles taken from the internet, as well as national and comparative legislation. As a result of the research, it is concluded that the stock corporation, although simplified, tends to be expensive to maintain and will not allow access to the capital market, as it will be a simplified stock corporation similar to the closed corporation, which does not have access to the capital market, unless it makes it listed through a difficult and expensive process. The foreign experience proved to be quite similar, as the legislation of all the States surveyed prohibits access to the capital market to simplified corporate types. The study offers as a contribution the information that the simplified companies in the studied States (Germany, Netherlands, United States of America, France and Colombia) experience the same limitations as the Brazilian medium and small companies for access to the capital market.